The tumor suppressor BAP1 cooperates with BRAFV600E to promote tumor formation in cutaneous melanoma. (24th September 2018) - Webster, Joshua D.; Pham, Trang H.; Wu, Xiumin; Hughes, Nicolas W.; Li, Zhongwu; Totpal, Klara; Lee, Ho‐June; Calses, Philamer C.; Chaurushiya, Mira S.; Stawiski, Eric W.; Modrusan, Zora; Chang, Matthew T.; et al.
Abstract: The deubiquitinating enzyme BAP1 is mutated in a hereditary cancer syndrome with a high risk of mesothelioma and melanocytic tumors. Here, we show that Bap1 deletion in melanocytes cooperates with the constitutively active, oncogenic form of BRAF (BRAF V600E ) and UV to cause melanoma in mice, albeit at very low frequency. In addition, Bap1 ‐null melanoma cells derived from mouse tumors are more aggressive and colonize and grow at distant sites more than their wild‐type counterparts. Molecularly, Bap1 ‐null melanoma cell lines have increased DNA damage measured by γH2aX and hyperubiquitination of histone H2a. Therapeutically, these Bap1 ‐null tumors are completely responsive to BRAF‐ and MEK‐targeted therapies. Therefore, BAP1 functions as a tumor suppressor and limits tumor progression in melanoma.